175. Implementation of Clinical Practice Guidelines for Care of Neonates With Necrotizing Enterocolitis Reduces Broad Spectrum Antibiotic Use in the Neonatal Intensive Care Unit. (26th November 2018) - Albert, Jonathan; Kaur, Ishminder; Bajwa, Geoffrey; Touch, Suzanne; Souder, Emily; Long, Sarah; Bhandari, Vineet
Abstract: Background: Exposure to broad spectrum antimicrobial agents (AA) is a known risk factor for colonization and infection with multidrug-resistant organisms (MDROs). Therapy with broad spectrum AAs is commonplace with no published guideline to help minimize their use in the NICU. We aimed to analyze clinical indications for the use of vancomycin and meropenem (V/M) in the NICU and the impact of a necrotizing enterocolitis (NEC) clinical practice guideline (CPG) on the use of V/M in the NICU. Methods: Patients who received V/M between January 2015 and December 2015 were identified using pharmacy administration data. Medical charts were reviewed retrospectively by two ID physicians to determine whether V/M were clinically indicated for each definitive course. A CPG outlining the optimal use of AAs for NEC was implemented in the NICU in our institution in August 2015 (Figure 1). We analyzed V/M DOT per 1, 000 patient-days before and after CPG implementation. There were no parallel changes in antimicrobial stewardship interventions. Results: At the start of V/M, mean gestation and chronologic age of the study population were 28.8 weeks and 26.9 days, respectively, and the mean weight was 2, 676 g. During the study period, 91 patients received 191 courses of vancomycin and 27 patients received 32 courses of meropenem; ~40% of V/M definitive use did not have a clear clinical indication (Table 1). Thirty-three percent of meropenem definitive use was in infants with NEC. During a 7-month baseline period, mean vancomycin and meropenem use was 105 and 56 DOTs per 1, 000 patient-days, respectively. Following NEC CPG implementation, mean vancomycin and meropenem use was 101 and 12 DOTs per 1, 000 patient-days, respectively (Figures 2 and 3). Conclusion: Widespread use of V/M was identified in the NICU. Following the implementation of NEC CPG, there was a decrease in the utilization of meropenem in the NICU. Disclosures: All authors: No reported disclosures.